Executive derailment, coaching and posttraumatic growth: reflections on practice guided by theory - Joseph, Stephen (Taylor & Francis, 2018)
The aim is to discuss the issue of executive career derailment in relation to posttraumatic stress disorder (PTSD) and the developing field of posttraumatic growth (PTG). There is much research on PTSD and PTG in a variety of contexts but as yet they remain to be applied to the experience of derailment. As such, in this paper I will provide a theoretical discussion of how PTSD and PTG are explained and linked to derailment. This will be followed by a reflection on the implications for how practitioners can help clients move forward following derailment. Understanding how derailment can be the springboard for personal and professional growth offers new opportunities for coaches to adopt a positive psychological mindset. PTG is an emerging area with implications for new research and the development of coaching in this important area of practice.